Effectiveness of Household Water Filtration Systems in Eliminating Plastic Particles: A Case Study from Mosul City, Iraq - Raghad N. Altaee; Kossay K. Al-Ahmady; Rasha Khalid Sabri Mhemid (Geography, Earth Science and Environment: Research Highlights Vol. 10, 2025)
On a global scale, plastic particles are a concern. The presence of microplastics (MPs) in tap water is becoming a global issue because of the risks associated with human consumption and health impacts on humans. Providing clean, safe drinking water may be challenging when MPs are present in drinking water, considered emerging pollutants. This study aimed to assess the presence and characteristics of MPs and to evaluate the removal efficiency (RE%) of household water filter systems (HWFS). The research was carried out in 12 sites in Mosul City. The identification of microplastics, as well as the morphological characterization (color, shape, and size) and analysis of polymer types, was performed by stereomicroscope, scanning electron microscopy (SEM) and Fourier transform spectroscopy (FTIR) techniques. The study revealed that the effectiveness of HWFS was between 93% and 30%, depending on several variables such as the age of the filter and the number of its stages. Fibers and fragments were the dominant morphotypes, comprising about 94% of all analyzed MPs. The transparent color accounting for about 52 % of the overall. Roughly 35% of MPs sizes were smaller than 10 µm. Around 58% of all considered polymer types corresponded to polyvinyl chloride (PVC), which was the highest percentage. In addition, PVC had the highest risk index compared to the other polymer types.